2010
DOI: 10.1016/j.neuroimage.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Imaging brain fatigue from sustained mental workload: An ASL perfusion study of the time-on-task effect

Abstract: During sustained periods of a taxing cognitive workload, humans typically display time-on-task (TOT) effects, in which performance gets steadily worse over the period of task engagement. Arterial spin labeling (ASL) perfusion functional magnetic resonance imaging (fMRI) was used in this study to investigate the neural correlates of TOT effects in a group of 15 subjects as they performed a 20-minute continuous psychomotor vigilance test (PVT). Subjects displayed significant TOT effects, as seen in progressively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
289
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(327 citation statements)
references
References 53 publications
30
289
7
1
Order By: Relevance
“…There was a significant main effect of time on RT (F = 3.101, P = 0.046) but no effect on accuracy (F = 1.034, P = 0.397). In previous studies, RT measures have been associated with fatigue from sustained mental workload [21,22]. In Figure 4, RT increases in a linear fashion from the beginning to the end of task performance (R 2 = 0.69), while there is a mild decline in accuracy.…”
Section: Rt and Accuracymentioning
confidence: 79%
“…There was a significant main effect of time on RT (F = 3.101, P = 0.046) but no effect on accuracy (F = 1.034, P = 0.397). In previous studies, RT measures have been associated with fatigue from sustained mental workload [21,22]. In Figure 4, RT increases in a linear fashion from the beginning to the end of task performance (R 2 = 0.69), while there is a mild decline in accuracy.…”
Section: Rt and Accuracymentioning
confidence: 79%
“…Studies utilizing the induced fatigue paradigm (in which elicited fatigue falls under the construct of 'primary fatigue' proposed by DeLuca, 2005b) have shown that higher-level cognitive control functions are particularly sensitive to detrimental induced fatigue effects (Lorist et al, 2000(Lorist et al, , 2005Van der Linden et al, 2003). Furthermore, sustained task performance has been shown to elicit a lasting decrease in cerebral blood flow in the fronto-parietal attention network in association with a fatigue-related reduction in performance (Lim et al, 2010). Therefore, we hypothesized middle-aged adults would show a reduction in load-related activation and an associated performance decrement (primarily at high levels of WM load) resulting from the exhaustion of cognitive resources in this age group at high levels of WM load, particularly in areas related to cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of extreme fatigue, it can take as long as 30 seconds for a production to fire (Gunzelmann et al, 2009). Microlapse theory posits that these lapses occur in central cognition based on a large body of research showing the impact of fatigue on the basal ganglia -where a recent fMRI study on the neural basis of the vigilance decrement, showed that the vigilance decrement activated a right fronto-parietal attentional network that lateralized to the basal ganglia and sensorimotor cortices (Lim et al, 2010).The result of microlapses is that productions will fire less reliably as time on task increases, causing a decreased likelihood of responding to a critical stimulus over time, with larger impacts when the signal duration is short. Gunzelmann et al (2009) also proposed a compensation mechanism for these microlapses.…”
mentioning
confidence: 99%